2021
DOI: 10.3389/fnagi.2021.649874
|View full text |Cite
|
Sign up to set email alerts
|

Brain Frequency-Specific Changes in the Spontaneous Neural Activity Are Associated With Cognitive Impairment in Patients With Presbycusis

Abstract: Presbycusis (PC) is characterized by preferential hearing loss at high frequencies and difficulty in speech recognition in noisy environments. Previous studies have linked PC to cognitive impairment, accelerated cognitive decline and incident Alzheimer’s disease. However, the neural mechanisms of cognitive impairment in patients with PC remain unclear. Although resting-state functional magnetic resonance imaging (rs-fMRI) studies have explored low-frequency oscillation (LFO) connectivity or amplitude of PC-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 66 publications
(74 reference statements)
0
7
0
Order By: Relevance
“…The close interaction between hearing loss and cognitive functions has gained attention of researchers recently ( Panza et al, 2019 ; Powell et al, 2021 ). On the one hand, neurocognitive functions have an impact on speech understanding, especially in challenging acoustic situations ( Rönnberg et al, 2013 ; Völter et al, 2020a , b ); on the other hand, several studies have pointed out the negative impact of hearing loss on cognition, both on a behavioral as well as on a neuroanatomic level ( Deal et al, 2015 ; Armstrong et al, 2020 ; Manno et al, 2021 ; Ren et al, 2021 ; Völter et al, 2021a ). A longitudinal study conducted by Lin in 2011 demonstrated that the risk of dementia within 11.9 years was elevated by 1.89 times in people with mild-hearing impairment, 3-fold in people with moderate hearing impairment, and by 4.94 times in people with severe hearing impairment ( Lin et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…The close interaction between hearing loss and cognitive functions has gained attention of researchers recently ( Panza et al, 2019 ; Powell et al, 2021 ). On the one hand, neurocognitive functions have an impact on speech understanding, especially in challenging acoustic situations ( Rönnberg et al, 2013 ; Völter et al, 2020a , b ); on the other hand, several studies have pointed out the negative impact of hearing loss on cognition, both on a behavioral as well as on a neuroanatomic level ( Deal et al, 2015 ; Armstrong et al, 2020 ; Manno et al, 2021 ; Ren et al, 2021 ; Völter et al, 2021a ). A longitudinal study conducted by Lin in 2011 demonstrated that the risk of dementia within 11.9 years was elevated by 1.89 times in people with mild-hearing impairment, 3-fold in people with moderate hearing impairment, and by 4.94 times in people with severe hearing impairment ( Lin et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…(2) slice timing; (3) realignment for head motion correction; (4) segmentation; (5) normalization to a standard template; (6) regressing six motion parameters, six temporal derivatives, and 12 corresponding squared items using the Friston-24 parameter; (7) smoothing with 8-mm full width at halfmaximum Gaussian kernel; and (8) detrending and filtering (0.01-0.08). Subjects with a translational or rotational head motion of >2.0 mm or 2.0 • in any direction were excluded.…”
Section: Data Processingmentioning
confidence: 99%
“…In terms of the global brain, cortical thinning and reduced gray matter volume have been found in ARHL subjects ( 5 , 6 ). Ren et al also found that abnormal spontaneous neural activity was frequency dependent and correlated with cognition by exploring all frequency bands of oscillation ( 7 ). Some studies have shown that the functional reorganization of the auditory cortex ( 8 ), cingulo-opercular network ( 9 ), motor ( 10 ), visual ( 11 ), and attention networks ( 12 ) in ARHL could be responsible for cognitive and neural functioning and, in turn, affect auditory processing.…”
Section: Introductionmentioning
confidence: 99%
“…Although impaired inner ear function is the main cause of ARHL, it is increasingly recognized that ARHL is also related to structural and functional changes in the central auditory pathway and other areas of the central nervous system (Kazee et al, 1995 ; Spongr et al, 1997 ; Salvi et al, 2002 ; Ouda et al, 2015 ). With the further application of functional magnetic resonance imaging (fMRI) which was based on blood oxygen level dependent (BOLD) in central nervous system abnormalities of ARHL, some studies have found that hearing loss devoted to the disrupted functional networks such as limbic network (SCLN), default mode network (DMN), executive control network (ECN), attention network (AN), and visual network (VN) (Chen et al, 2018 , 2020 ; Xing et al, 2020 , 2021a , b ; Ren et al, 2021 ). In addition, experiments have found abnormal structural and functional visual centers similar to the auditory center in ARHL (Schulte et al, 2020 ; Wei et al, 2021 ), proving that the dysfunction caused by hearing loss involves the whole brain (Benetti et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies using magnetic resonance spectroscopy (MRS) have shown decreased neurotransmitters such as gamma-aminobutyric acid (GABA) in ARHL related to age and speech in noise, indicating that the reduction of neurotransmitters in the auditory system is related to functional impairment (Gao et al, 2015 ; Dobri and Ross, 2021 ). Many fMRI studies and animal experiments have linked the decline of cognition with functional abnormalities in ARHL, as well as dementia and depression (Chen et al, 2020 ; Choi et al, 2021 ; Ren et al, 2021 ; Shen et al, 2021 ). However, the causal relationship between the degeneration of peripheral auditory system, such as inner ear structure, and the declined function of central auditory system and cognitive function in patients has not been clear (Rutherford et al, 2018 ; Bowl and Dawson, 2019 ; Ralli et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%